Influence of surface morphology of porous templates TiO2 //X (X = Si, Ti) on structure and magnetic properties of Co/Pd multilayered films - Wu, Wen-Bin; Kasiuk, Julia V.; Fedotova, Julia A. (Journal of the Belarusian State University. Physics, 2019)
In the present research, multilayered Co/Pd films were deposited on the porous TiO2 templates obtained on different substrates - silicon wafers (Si) and titanium foil (Ti), in order to conserve a high effect of perpendicular magnetic anisotropy characterizing the corresponding continuous films. The results of the magnetometric analysis show that the multi-layered films deposited on the porous TiO2 templates on Si wafers demonstrate good perpendicular magnetic anisotropy with a relatively high remanent magnetization (Mr/MS = 0.85) and twice higher coercive field (HChard = 176.6 kA/m) compared to the corresponding continuous film on Si wafer (reference film). The obtained parameters open up the possibility to apply these films for designing various spintronic devices and perpendicular magnetic recording media.
Keywords: multilayered Co/Pd films; porous TiO2 templates; perpendicular magnetic anisotropy; magnetization reversal